Understanding morphology effects on fill factor losses in dilute-donor organic solar cells. (1st December 2022) - Kramer, Aaron; Kaiser, Waldemar; Zhang, Boya; Murthy, Lakshmi N.S.; Gagliardi, Alessio; Hsu, Julia W.P.; Vandenberghe, William G.
Abstract: Experimental results of organic solar cells with low donor concentrations using small molecule donors have displayed significantly lower fill factors (FFs) compared to dilute-donor solar cells (DDSCs) with polymer donors. We perform experiments and kinetic Monte Carlo simulations, to understand the observed FF discrepancy and how FF can be improved. Our results reveal that small molecule DDSCs collect holes from the region of the active layer near the anode whereas polymer DDSCs collect holes from a deeper volume inside the active layer. This enlarged collection region is facilitated by the morphology of polymer chains extending from the anode into the active layer. The chains permit holes to hop along the donor sites to the anode with no barrier. Small molecule DDSCs, in contrast, require a large electric field to transfer holes from isolated donor sites back to the acceptor matrix to reach the anode. Collections in small molecule DDSCs are thus constrained to photogenerated holes on donors near the anode. We propose strategies to increase DDSC FF to levels comparable to bulk-heterojunction organic solar cells by decreasing the donor-acceptor highest occupied molecular orbital energy offset, or by engineering the active layer morphology so that a higher density of donors are in proximity/contact with the anode. Graphical Abstract: ga1 Highlights: Low dilute-donor FFs are the result of a large highest occupied molecular orbital (HOMO) energy offset and poor donor proximity to the anode. In small molecule dilute-donors, a large electric field is required to transfer a hole from the donor back to the acceptor before recombination due to poor donor proximity to the anode. The photoactive region where the large electric field can be sustained is very small and gets even smaller with increasing bias, giving rise to a low FF in small molecule dilute-donor solar cells. In polymer dilute-donor solar cells, a large electric field is not required as holes can avoid recombination by moving along polymer chains towards the anode.